2023
DOI: 10.3390/su15086862
|View full text |Cite
|
Sign up to set email alerts
|

European Citizens’ Worries and Self-Responsibility towards Climate Change

Abstract: Attitudes and perceptions about climate change (CC) are crucial to public engagement and support in the promotion of mitigating actions and sustainable lifestyles embracing the United Nations’ sustainable development goals. This study aimed to investigate how worried are European citizens about CC, and what is their willingness to assume self-responsibility in its mitigation. We used the European Social Survey, namely the answers to the questions “How worried are you about climate change?” and “To what extent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…It has been previously reported that, in Europe, concern and responsibility for CC are more intense by women than men (Mata et al 2023), which can be explained by the "conservative male" effect, or the higher frequency of male conservationists, as discussed by (Jylhä et al 2016). In this study, the probability of a European citizen perceiving CC causes as natural processes is higher men than in women.…”
Section: Discussionsupporting
confidence: 44%
“…It has been previously reported that, in Europe, concern and responsibility for CC are more intense by women than men (Mata et al 2023), which can be explained by the "conservative male" effect, or the higher frequency of male conservationists, as discussed by (Jylhä et al 2016). In this study, the probability of a European citizen perceiving CC causes as natural processes is higher men than in women.…”
Section: Discussionsupporting
confidence: 44%
“…Worry motivates cognitive and analytical processing of risk perception, more intensely. Mata et al (2023) found the same in relation to European citizens.…”
Section: Discussionmentioning
confidence: 57%
“…Studies have also shown that individuals with a higher perception of the CC risks, and more worried about the CC consequences, incite change in behaviors and increase their willingness to pay for CC mitigation ( Brulle, Carmichael & Jenkins, 2012 ; Mata et al, 2023 ; Mayer & Smith, 2019 ). Other studies ( Leiserowitz, 2006 ; O’Connor, Bard & Fisher, 1999 ; Smith & Leiserowitz, 2014 ) have shown the relationship between worried individuals about CC and the belief in the adoption of CC mitigating measures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations